2018
DOI: 10.1371/journal.pone.0193810
|View full text |Cite
|
Sign up to set email alerts
|

Biomolecular study of human thymidylate synthase conformer-selective inhibitors: New chemotherapeutic approach

Abstract: Thymidylate synthase (TS) is a well-validated target for the therapy of adult cancers. Propane-1,3-diphosphonic acid (PDPA) has significant inhibitory properties against human thymidylate synthase (hTS) relative to mouse TS which is not predicted to adopt an inactive conformer. The current research aims to identify novel, lead inhibitors of hTS and examine the prediction that they bind selectively to hTS enzymes existing in different conformational equilibria. Conformer-selectivity was evaluated through perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Compounds which are structural analogues of thymidylate synthase substrates, such as 5-fluorouracil, combine with TS to form inactive complexes. This leads to the depletion of thymidylic acid in the cells, which results in the inhibition of their division and ultimately death [59,60]. DNA synthesis in cancer cells is higher than in normal cells; therefore, thymidylate synthase inhibitors constitute an important group of anti-cancer drugs.…”
Section: Anti-proliferative Effects Of 134-oxadiazole Derivativesmentioning
confidence: 99%
“…Compounds which are structural analogues of thymidylate synthase substrates, such as 5-fluorouracil, combine with TS to form inactive complexes. This leads to the depletion of thymidylic acid in the cells, which results in the inhibition of their division and ultimately death [59,60]. DNA synthesis in cancer cells is higher than in normal cells; therefore, thymidylate synthase inhibitors constitute an important group of anti-cancer drugs.…”
Section: Anti-proliferative Effects Of 134-oxadiazole Derivativesmentioning
confidence: 99%
“…13,14 Some studies have shown that raltitrexed has antitumor effects on a variety of cancers. [14][15][16] Recently, a prospective study has shown that raltitrexed plus oxaliplatin-based TACE could be effective with few adverse reactions in the treatment of unresectable HCC. 17 Each patient completed the informed consent form for TACE.…”
Section: Introductionmentioning
confidence: 99%
“…Limitations. The exact mechanism of the novel bacterial strains biological activity to be characterized and more characterization(s) if they could prove chemotherapeutic effects (El-Mesallamy et al, 2018) based on the bio-degradation products predicted downstream target enzymes or membrane proteins/receptors.…”
Section: Discussionmentioning
confidence: 99%